Space-charge-limited electron and hole currents in hybrid organic-inorganic perovskites - Mohammad Sajedi Alvar (Nature Portfolio, 2020)
Space-charge-limited currents are widely used to characterize charge transport in semiconductors. Here, the authors characterize space-charge-limited electron and hole currents in metal-halide perovskites, applicable in emerging solar cells. The currents are strongly influenced by the high permittivity and ion motion.